Complexation of multiple mineral elements by fermentation and its application in laying hens - Chen, Huayou; Heng, Xinyu; Li, Keyi; Wang, Zhen; Ni, Zhong; Gao, Ebin; Yong, Yangchun; Wu, Xin (Frontiers in Nutrition, 2022)
To overcome the problems with current mineral supplements for laying hens including low absorption, mineral antagonism, and high cost, we developed mineral element fermentation complexes (MEFC) by synergistically fermenting bean dregs and soybean meal with strains and proteases and complexing with mineral elements. The fermentation complexation process was optimized based on the small peptide and organic acid contents and the complexation rate of mineral elements after fermentation. The optimal conditions were as follows: the total inoculum size was 5% (v/w), 15% (w/w) wheat flour middling was added to the medium, and mineral elements (with 4% CaCO3) were added after the completion of aerobic fermentation, fermentation at 34°C and 11 d of fermentation. Under these conditions, the complexation rates of Ca, Fe, Cu, Mn, and Zn were 90.62%, 97.24%, 73.33%, 94.64%, and 95.93%, respectively. The small peptide, free amino acid, and organic acid contents were 41.62%, 48.09 mg/g, and 183.53 mg/g, respectively. After 60 d of fermentation, 82.11% of the Fe in the MEFC was ferrous ions, indicating that fermentation had a good antioxidant effect on ferrous ion, and the antioxidant protection period was at least 60 days. Fourier transform infrared spectroscopy showed that the mineral ions were complexed with amino and carboxyl groups. The added mineral elements promoted microbial growth, protein degradation, and organic acid secretion and significantly improved fermentation efficiency. Animal experiments showed that MEFC had positive effects on several parameters, including production performance (average daily feed intake, P < 0.05; egg production rate, P < 0.05; and average egg weight, P < 0.05), mineral absorption, intestinal morphology (villus height to crypt depth ratio in the jejunum and ileum, P < 0.05), and blood routine and biochemical indexes (red blood cells, P < 0.05; hemoglobin, P < 0.05). This study provides theoretical support for the development of mineral complexes for laying hens via fermentation.